Fuzzy Predator-prey Systems By Extended Runge-kutta Method With Polynomial Interpolation Technique - Nor Atirah Izzah Zulkefli; Yeak Su Hoe; Nor Afifah Hanim Zulkefli (Semarak Ilmu Publishing, 2024)
Non-Indexed Publication